Role of glycosyltransferases modifying type B flagellin of emerging hypervirulent Clostridium difficile lineages and their impact on motility and biofilm formation - Valiente,E; Bouche,L; Hitchen,P; Faulds-Pain,A; Songane,M; Dawson,LF; Donahue,E; Stabler,RA; Panico,M; Morris,HR; Bajaj-Elliott,M; Logan,SM; et al. (Journal of Biological Chemistry, 2016)
Clostridium difficile is the principal cause of nosocomial infectious diarrhea worldwide. The pathogen modifies its flagellin with either a type A or type B O-linked glycosylation system, which has a contributory role in pathogenesis. We study the functional role of glycosyltransferases modifying type B flagellin in the 023 and 027 hypervirulent C. difficile lineages by mutagenesis of five putative glycosyltransferases and biosynthetic genes. We reveal their roles in the biosynthesis of the flagellin glycan chain and demonstrate that flagellar post-translational modification affects motility and adhesion-related bacterial properties of these strains. We show that the glycosyltransferases 1 and 2 (GT1 and GT2) are responsible for the sequential addition of a GlcNAc and two rhamnoses, respectively, and that GT3 is associated with the incorporation of a novel sulfonated peptidyl-amido sugar moiety whose structure is reported in our accompanying paper (Bouché, L., Panico, M., Hitchen, P., Binet, D., Sastre, F., Faulds-Pain, A., Valiente, E., Vinogradov, E., Aubry, A., Fulton, K., Twine, S., Logan, S. M., Wren, B. W., Dell, A., and Morris, H. R. (2016) J. Biol. Chem. 291, 25439–25449). GT2 is also responsible for methylation of the rhamnoses. Whereas type B modification is not required for flagellar assembly, some mutations that result in truncation or abolition of the glycan reduce bacterial motility and promote autoaggregation and biofilm formation. The complete lack of flagellin modification also significantly reduces adhesion of C. difficile to Caco-2 intestinal epithelial cells but does not affect activation of human TLR5. Our study advances our understanding of the genes involved in flagellar glycosylation and their biological roles in emerging hypervirulent C. difficile strains.